Determination of 93Zr in radioactive waste from nuclear power plants using Inductively Coupled Plasma Mass Spectrometry (Brazilian Journal of Radiation Sciences, 2018)
The zirconium isotope 93Zr is a long-lived pure β-particle-emitting radionuclide produced from 235U fission and from neutron activation of the stable isotope 92Zr and thus occurring as one of the radionuclides found in nuclear reactors. Due to its long half-life, 93Zr is one of the radionuclides of interest for the performance of assessment studies of waste storage or disposal. This paper describes the determination of 93Zr in evaporator concentrate (EC) sample from nuclear power plant (PWR). A zirconium selective separation using liquid-liquid extraction and TRU column were used before the ICPMS measurement to remove isobaric interferences.20-21 93Nb detection limit of 0.045 μg L-1 was obtained for 93Zr determination by ICPMS technique.